Sproul, R. C. Defending Your Faith: An Introduction to Apologetics - Tiur M.O. Saragih (Universitas Pelita Harapan, 2019)
Sproul, R. C. Defending Your Faith: An Introduction to Apologetics. Wheaton: Crossway, 2009. 208 pages. 10.99.